High-sensitivity Troponin I Assay for Early Detection of Myocardial Injury in Carbon Monoxide Intoxication - Tsung-Neng Tsai; Chih-Hao Shen; Gen-Min Lin; Pang-Yen Liu; Ming-Yueh Liu; Li-Yen Huang (Journal of Medical Sciences, 2024)
Background: Carbon monoxide (CO) intoxication is the most common gas-related event resulting in emergency room (ER) visits, often leading to myocardial injuries measured through the assessment of troponin levels. Recent efforts have focused on developing high-sensitivity troponin assays for more accurate acute myocardial infarction diagnosis. However, studies using high-sensitivity troponin I (hs-TnI) assays to identify myocardial injury following CO intoxication are lacking. Aim: We compared the measurement of circulating troponin I levels using the hs-TnI assay and the contemporary troponin I (cTnI) assay. Methods: We prospectively analyzed 50 patients with CO intoxication who were admitted to the ER between September 2012 and October 2013. Clinical, demographic, electrocardiographic (ECG), echocardiographic, and laboratory data were compared. Circulating troponin I levels were measured using hs-TnI and cTnI assays upon arrival in the ER and 24, 48, and 72 h after admission. Results: Most patients with moderate or severe CO intoxication had elevated circulating troponin I levels, as detected using the hs-TnI assay. In addition, none of the results above or below the cutoff value for circulating troponin I changed from those found in the ER. In the cTnI assay, elevated circulating troponin I above the cutoff value in the ER was detected in 21 of 36 patients (58%). Participants with elevated troponin I levels, as measured by the hs-TnI assay, were more likely to experience various unfavorable clinical outcomes. Conclusion: The hs-TnI assay can detect elevated circulating troponin I levels earlier than the cTnI assay in patients with CO intoxication and myocardial injury.